Mechanical properties and setting characteristics of geopolymer mortar using styrene-butadiene (SB) latex. (15th June 2016) - Lee, N.K.; Kim, E.M.; Lee, H.K.
Highlights: The fastest initial and final setting time were 9 min and 70 min, respectively. The addition of SB latex resulted in the 50% improvement in the flexural strength. The bonding strength and thermal conductivity were 1.9 MPa and 0.5 W/(m·K), respectively. Abstract: The present study assesses the mechanical properties and setting characteristics of geopolymer mortar using styrene-butadiene (SB) latex. Fly ash/slag based geopolymer mortar incorporating SB latex was fabricated, and their setting time, early-age compressive strength and flexural strength were measured in an effort to determine the optimum alkali modulus (SiO2 /Na2 O) of alkali-activator and slag contents in geopolymer. The fastest setting time was achieved by the geopolymer mortar with the slag content of 30% and alkali modulus of 2.27 as exhibiting the initial and final setting time of 9 min and 70 min, respectively. The flexural strength was improved by 50% when the addition of SB latex increased from 0% to 10% due the enhanced bonding interactions of the geopolymer matrix. Based on the derived mix proportions, the bonding strength and thermal conductivity of the rapid setting geopolymer mortar were examined. The geopolymer mortar incorporating 10% SB latex showed the highest bonding strength of 1.93 MPa when using epoxy resin at the interface and the thermal conductivity of 0.506 W/(m·K).